REGIONAL PRIORITIES FOR EDUCATION DEVELOPMENT - Aurel-Gabriel, SIMIONESCU; Mariana-Carmelia, DRAGOMIR (Strategii Manageriale, 2013)
Often worded, the competence of coordination and stimulating the development in a larger scale, is the most visible prerogative of regional level and relates to territorial dimension (in the present context we are talking about territories of 30,000 km2) and population (on average about 2.5 million people). The fulfillment of this goal must be preceded by a series of public policies and strategies specific to the region, but obviously with references and localization in the national strategies that should meet the general framework in which the regional level should be able to carry out their initiatives depending on specific priorities, competitive advantages, population requirements, local possibilities, etc. and of course taking into account European regional development, the way the territorial administrative entities work and act at European level and the need for complex activities of European countries, generally, during this period.